Combination of Interleukin-15 With a STING Agonist, ADU-S100 Analog: A Potential Immunotherapy for Prostate Cancer - Esteves, Ana M.; Papaevangelou, Efthymia; Dasgupta, Prokar; Galustian, Christine (Frontiers in Oncology, 2021)
Prostate cancer is the second most commonly diagnosed cancer in men with mortality rates, overtaking those for breast cancer in the last 2 years in the UK. Despite advances in prostate cancer treatments, over 25% of men do not survive over 5 years with advanced disease. Due to the success of immunotherapies in treating other cancers, this treatment modality has been investigated for Prostate cancer, however, the sole FDA approved immunotherapy so far (Provenge™) only extends life by a few months. Therefore, finding immunotherapeutic agents to treat prostate cancer is of major interest. Our group has previously shown that Interleukin-15 (IL-15), unlike other therapeutic cytokines such as IL-2 and IL-12, can stimulate expansion and activity of CD8 T cells and NK cells in vitro when they are exposed to prostate cancer cells, while studies in mice have shown a 50% reduction in tumor size with no apparent toxicity. In this study, we aim to examine potencies of IL-15 in combination with a cyclic dinucleotide (CDN) that activates the Stimulator of Interferon-Gene (STING) receptor. Selected CDNs (also known as STING agonists) have previously been shown to activate both T cells and dendritic cells through STING. We hypothesize that the combination of STING agonists and IL-15 can additively increase NK and T cell activity as they act to increase type I interferons (IFNs) through STING activation and IFN-γ through IL-15. In prostate cancer-lymphocyte co-cultures we now show that combination of IL-15 and the STING agonist ADU-S100 analog induces a marked killing of cancer cells above that seen with IL-15 or ADU-S100 alone. We show that this is related to a potent activation of NK cells resulting in increased perforin and CD69 expression, and up to a 13-fold increase in IFNγ secretion in the co-cultures. NK cells are responsible for killing of the cancer cells, as shown by a lack of cytotoxicity in NK depleted lymphocyte-tumor cell co-cultures, or in co-cultures of B and T cells with tumor cells. In summary, we propose that the combination of IL-15 and the sting agonist ADU-S100 analog may be potently effective in treatment of prostate cancer.